1968
DOI: 10.1071/ch9680827
|View full text |Cite
|
Sign up to set email alerts
|

A multilayer model of a solid-regular solution interface

Abstract: A multilayer model of the interface between a solid and a regular solution has been developed by treating the solution phase in the grand canonical ensemble. The partition functions necessary for the evaluation of the grand partition function are obtained using either the quasi-chemical or Bragg-Williams approximations. The equilibrium concentration profile normal to the interface is then found from the maximum term in the multiple sum for the grand partition function. The adsorption, surface tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

1969
1969
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(19 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…Density functional calculations performed by Röcken et al (8) and similar calculations for adsorption of an associating fluid (14) have revealed some details of the phase diagrams. One should perhaps mention that the DF calculations for continuous systems have been also confirmed (15) by the calculations based on a mean-field type theory (16)(17)(18) for lattice systems with nearest-neighbor interactions. However, neither DF calculations for the continuous system nor the mean-field calculations for the lattice system have been compared with relevant computer simulation studies.…”
Section: Introductionmentioning
confidence: 95%
“…Density functional calculations performed by Röcken et al (8) and similar calculations for adsorption of an associating fluid (14) have revealed some details of the phase diagrams. One should perhaps mention that the DF calculations for continuous systems have been also confirmed (15) by the calculations based on a mean-field type theory (16)(17)(18) for lattice systems with nearest-neighbor interactions. However, neither DF calculations for the continuous system nor the mean-field calculations for the lattice system have been compared with relevant computer simulation studies.…”
Section: Introductionmentioning
confidence: 95%
“…. , liquids (18). Recently, this approach has been expanded to enable predictions for adsorption on porous solids (19), for r a ( N a ) for molecules of species a.…”
Section: Introductionmentioning
confidence: 99%
“…No more than one molecule is permitted at a given lattice site, and each pair of molecules in adjacent sites contributes ε to the potential energy. It can be shown (11)(12)(13)(14) that in the mean-field approximation the grand potential of the system is = (ε/2) …”
mentioning
confidence: 99%